Ethical Leadership Behaviours of School Administrators from Teachers' Point of View - Ozan, Mukadder Boydak; Ozdemir, Tuncay Yavuz; Yirci, Ramazan (Fahrenhouse, 2017)
The main objective of this study is to determine the degree of ethical leadership behaviours of school administrators according to teachers' opinions. As a quantitative research, this study was carried out in the academic year of 2010-2011 with 371 teachers who were employed in elementary schools. Ethical Leadership Questionnaire developed by Langlois (2007) has been used in the research. Findings of study reveal that as the year of seniority increases, more teachers think that administrators act within the ethical standards. Teachers' opinions about school administrators' ethical leadership behaviours do not differentiate according to the teachers' gender variable. However; in terms of branch variable, a significant difference is observed in teachers' opinions about their school administrators' ethical leadership behaviours when they faced with an ethical problem. Class teachers' opinions are more positive than branch teachers' opinions regarding school administrators' ethical leadership behaviours. Results indicate that teachers think that their school administrators often faced with an ethical dilemma while deciding upon personnel issues. This study concludes that establishing written ethical codes for school administrators may help them to make decisions with integrity, fairness, and in a more ethical manner especially about personnel issues.
Keywords: ethical leadership; school principals; ethical decision; teachers